2020
DOI: 10.1099/jmm.0.001203
|View full text |Cite
|
Sign up to set email alerts
|

Potential RNA-dependent RNA polymerase inhibitors as prospective therapeutics against SARS-CoV-2

Abstract: Introduction. The emergence of SARS-CoV-2 has taken humanity off guard. Following an outbreak of SARS-CoV in 2002, and MERS-CoV about 10 years later, SARS-CoV-2 is the third coronavirus in less than 20 years to cross the species barrier and start spreading by human-to-human transmission. It is the most infectious of the three, currently causing the COVID-19 pandemic. No treatment has been approved for COVID-19. We previously proposed targets that can serve as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 50 publications
(87 reference statements)
1
45
0
Order By: Relevance
“…The cryo-electron microscopic structure of the SARS-CoV-2 polymerase complex consisting of nsp12 (RdRp), nsp7, and nsp8 was reported in May 2020 [ 33 ]. Virtual screening has selected many approved drugs that were anticipated to bind to RdRp, including nilotinib, saquinavir, tipranavir, lonafarnib, tegobuvir, olysio, cepharanthine, filibuvir, ornipressin, lypressin, examorelin, polymyxin B1, nacortocin, cistinexine, cisatracurium, bedoradrine, palbociclib, quinupristin, dactinomycin, sirolimus, cetrorelix, rifampin, nebivolol, and sofosbuvir [ [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: In Silico Approachmentioning
confidence: 99%
“…The cryo-electron microscopic structure of the SARS-CoV-2 polymerase complex consisting of nsp12 (RdRp), nsp7, and nsp8 was reported in May 2020 [ 33 ]. Virtual screening has selected many approved drugs that were anticipated to bind to RdRp, including nilotinib, saquinavir, tipranavir, lonafarnib, tegobuvir, olysio, cepharanthine, filibuvir, ornipressin, lypressin, examorelin, polymyxin B1, nacortocin, cistinexine, cisatracurium, bedoradrine, palbociclib, quinupristin, dactinomycin, sirolimus, cetrorelix, rifampin, nebivolol, and sofosbuvir [ [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: In Silico Approachmentioning
confidence: 99%
“…Enisamium was shown to inhibit the activity of the SARS-CoV-2 RNA polymerase and its active metabolite exhibits similar efficacy with remdesivir triphosphate, it is approved in 11 countries and does not require intravenous administration, unlike remdesivir ( Walker et al, 2020 ). In silico approaches have also been used to identify novel inhibitors, either by screening clinically used polymerase inhibitors, or FDA approved drugs and/or natural compounds ( Kar et al, 2020 ; Pokhrel et al, 2020 ; Ruan et al, 2020 ; Zhang et al, 2020b ).…”
Section: Non-structural Proteins As Potential Drug Targetsmentioning
confidence: 99%
“…Computer-aided drug screening is being extensively used to discover new drugs and repurpose existing ones targeting RdRp in order to treat COVID-19. in silico virtual screening by Pokhrel et al indicated that quinupristin bound across the conserved RNA tunnel of RdRp, possibly resulting in the arrest of viral replication (64). Elfiky cited ribavirin, sofosbuvir, remdesivir, tenofovir, galidesivir, and the guanosine derivative (IDX-184) as potent drugs for COVID-19 therapy since they tightly bind to SARS-CoV-2 RdRp in a model (65).…”
Section: Potential Therapeutic Agents Targeting Rdrpmentioning
confidence: 99%